High Depolarization Ratios of Naturally Occurring Cirrus Clouds Near Air Traffic Regions Over Europe. Issue 23 (14th December 2018) - Urbanek, Benedikt; Groß, Silke; Wirth, Martin; Rolf, Christian; Krämer, Martina; Voigt, Christiane
Abstract: Cirrus clouds have a large influence on the Earth's climate and anthropogenic activities such as aviation can alter their properties. Besides the formation of contrails, indirect effects on naturally occurring cirrus like increased heterogeneous freezing due to exhaust soot particles are discussed in the literature. However, hardly any observational study exists. In this work we present cirrus optical properties measured by an airborne lidar over Europe during the Midlatitude Cirrus experiment (ML‐CIRRUS). One half of the cloud cases showed elevated depolarization ratios with a mode difference of 10 percentage points indicating differences in the clouds microphysical properties. Their origin can be traced back to highly frequented air traffic regions, and they show lower in‐cloud ice supersaturations. Our analysis reveals no influence of embedded contrails and temperature. These results could be explained by an indirect aerosol effect where heterogeneous freezing is caused by aviation exhaust particles. Plain Language Summary: Civil airplanes emit exhaust gases and soot into the atmosphere, which can influence the Earth's climate in several ways. One possibility could be that emitted soot particles alter the formation of ice clouds, which has a potentially high climate impact. However, observational studies of this process are sparse. In this work we present ice clouds measured above Europe by an airborne remote sensing instrument. One group of clouds features elevated depolarization ratios implying altered crystal habits. It also shows lower ice supersaturation indicating a modified ice formation. We demonstrate that this is not caused by condensation trails present inside the clouds, by temperature, or by the dynamical state of the atmosphere. However, these clouds had formed in air that stemmed from highly frequented aviation corridors. Thus, our observations could be the first traces of this indirect process. Key Points: We found two types of cirrus clouds in the Northern Hemisphere midlatitudes; one shows significantly higher depolarization ratios These clouds also exhibit lower in‐cloud supersaturations and can be traced back to aviation corridors Our analysis demonstrates that heterogeneous freezing on aviation exhaust particles could explain these results